1990
DOI: 10.1136/ard.49.8.624
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of oral corticosteroids on bone mineral density in systemic lupus erythematosus: a preliminary study with dual energy x ray absorptiometry.

Abstract: Dual energy x ray absorptiometry and a wide range of blood and urine tests were used to assess the propensity ofpatients with systemic lupus erythematosus to develop an impairment of bone mineral density. Surprisingly, in this preliminary study no significant differences in bone mineral density were found when patients taking 10 mg or more of prednisolone for six months or longer were compared with those who had never taken prednisolone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
2
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 13 publications
4
38
2
4
Order By: Relevance
“…Steroids are a mainstay drug therapy in JDM and are a well-recognized cause of osteoporosis in other rheumatic diseases (17)(18)(19)(20)(21)(22)(23). Differently from other reports, our study showed that in children with JDM there is no significant correlation between bone mass and steroid use, a fact possibly due to the small number of patients included in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…Steroids are a mainstay drug therapy in JDM and are a well-recognized cause of osteoporosis in other rheumatic diseases (17)(18)(19)(20)(21)(22)(23). Differently from other reports, our study showed that in children with JDM there is no significant correlation between bone mass and steroid use, a fact possibly due to the small number of patients included in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…Multiple causes have been proposed to contribute to osteopenia, including limited physical activity, immobility, limited exposure to sunlight, systemic inflammation, corticosteroid use, delay in pubertal development, inadequate dietary intake of calcium and vitamins, and renal insufficiency (3,(5)(6)(7)(8)(9)(10). Although there is no consensus about the extent of the impact of these factors on bone mineral density (BMD) in children with rheumatic diseases, it is important to understand their implications in order to plan further strategies to prevent and treat bone disease in these children.…”
Section: Introductionmentioning
confidence: 99%
“…to date, low BMD has been particularly associated with patients treated with corticosteroids [4,5]. the predominant trabecular loss in corticosteroid-treated Sle patients may be partially explained by the effects of this therapy on mineral bone.…”
Section: Discussionmentioning
confidence: 95%
“…Previous cross-sectional studies have demonstrated that older age, postmenopausal state, low body mass index, longer Sle disease duration, organ damage, impaired renal function, markers of inflammation, low 25-hydroxyvitamin D (25(OH) D) serum levels, and number of deliveries are risk factors for low bone mass density (BMD) [4]. Regardless to the Sle therapy, some studies with Sle patients had shown corticosteroid-induced bone loss [4], but others failed to detect any difference [5,6]. Disease damage and disease severity had been associated with bone loss in the lupus population [6,7].…”
Section: Introductionmentioning
confidence: 95%